PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPEMIMPINAN TRANSAKSIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) KARYAWAN RSKJ PROVINSI BENGKULU - Novianti, Rike; Herfianti, Meiffa (Universitas Prof. Dr. Hazairin SH, 2024)
Leadership is the main key to the success of a company in achieving a goal. A company requires appropriate transformational leadership and transactional leadership to encourage the emergence of organizational citizenship behavior in each employee. The purpose of this research is to determine the influence of transformational leadership and transactional leadership on organizational citizenship behavior (OCB) in RSKJ employees in Bengkulu Province. The population that will be used in this research is employees of the RSKJ nursing section of Bengkulu Province, totaling 100 employees. This research uses a nonprobability sampling technique with the technique taken, namely saturated sampling (census). Saturated sampling technique is a sample determining technique when all members of the population are used as samples. So the sample used in this research was 100 employees of the RSKJ nursing section of Bengkulu Province. This research uses quantitative methods and data collection techniques by means of observation and distributing questionnaires. Then the questionnaire data was processed using SPSS version 26. Based on the results of this research, it can be concluded that the results of hypothesis testing from the t test (partial) and F test (simultaneous) have a positive and significant effect on the transformational leadership and transactional leadership variables on organizational citizenship behavior.